2018
DOI: 10.1007/s00737-018-0883-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal depression on perinatal outcomes in hospitalized women—a prospective study

Abstract: Scarce data exists regarding the prevalence of antenatal depression in hospitalized pregnant women, and its effect on perinatal outcome. We aimed to estimate the risk of maternal depression among women hospitalized in a high-risk pregnancy department, and to evaluate its potential association with adverse perinatal outcome. A depression screening self-questionnaire-based prospective study was performed, in which hospitalized pregnant women who screened positive for depression were compared to those who screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 25 publications
0
42
1
4
Order By: Relevance
“…Women who were hospitalized in the high-risk pregnancy units before the COVID-19 pandemic (between November 2016 and April 2017) served as the comparison group. The comparison group was composed of women who were recruited for previous study performed in the same high-risk pregnancy units [ 11 ]. High risk pregnancy was defined according to the Israeli Ministry of Health statement regarding criteria for high-risk pregnancy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Women who were hospitalized in the high-risk pregnancy units before the COVID-19 pandemic (between November 2016 and April 2017) served as the comparison group. The comparison group was composed of women who were recruited for previous study performed in the same high-risk pregnancy units [ 11 ]. High risk pregnancy was defined according to the Israeli Ministry of Health statement regarding criteria for high-risk pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected in a cross-sectional format, at two time points. Data regarding the comparison group were collected as part of a previous prospective study that was taken in the same high-risk units [ 11 ]. The group of women which served as the “unexposed” group was available from an historic study [ 11 ], and so the sample size of this group was fixed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors reported that women interacted more with the fetus as well as faced a greater risk of isolation from their families [25,73,77,138,139]. Previous studies highlighted that some of the most prevalent depressive episodes were reported by women [50,138,140,141]. Women with depressive symptoms tended to report lower caring toward the fetus [119], to become more ambivalent regarding the future baby, to express more negative comments, to dislike their bodies, and to be less involved in pregnancy [6,73,142,143].…”
Section: Gender Differencesmentioning
confidence: 99%
“…Gebelikte anne ve fetüsle ilgili sağlık problemlerinin ortaya çıkması ya da risk yaratan bir komplikasyon gelişmesi ve bu sebeple hastaneye yatma, yaşanan belirsizlik, hastane ortamı, yalnızlık duygusu, iş yaşantısı ve sosyal çevreden ayrı kalma gibi nedenlerle anksiyete ve depresyonun daha da artmasına sebep olmaktadır [5,6]. Yüksek riskli gebelerde anksiyete ve depresyon prevalansı ile ilgili yapılmış çalışmalar incelendiğinde anksiyete %12-41 [7][8][9], depresyon %7-47 [7,[10][11][12] oranlarında görülmektedir.…”
Section: Introductionunclassified